Mechanisms of Ferroptosis and Emerging Links to the Pathology of Neurodegenerative Diseases - Sun, Yiyan; Xia, Xiaohuan; Basnet, Diksha; Zheng, Jialin C.; Huang, Jian; Liu, Jianhui (Frontiers in Aging Neuroscience, 2022)
Neurodegenerative diseases are a diverse class of diseases attributed to chronic progressive neuronal degeneration and synaptic loss in the brain and/or spinal cord, including Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis and multiple sclerosis. The pathogenesis of neurodegenerative diseases is complex and diverse, often involving mitochondrial dysfunction, neuroinflammation, and epigenetic changes. However, the pathogenesis of NDDs has not been fully elucidated. Recently, accumulating evidence revealed that ferroptosis, a newly discovered iron-dependent and lipid peroxidation-driven type of programmed cell death, provides another explanation for the occurrence and progression of neurodegenerative diseases. Here, we provide an overview of the process and regulation mechanisms of ferroptosis, and summarize current research progresses that support the contribution of ferroptosis to the pathogenesis of neurodegenerative diseases. A comprehensive understanding of the emerging roles of ferroptosis in neurodegenerative diseases will shed light on the development of novel therapeutic technologies and strategies for slowing down the progression of these diseases.